(3TQM dGejI GdYLes - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s; (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdbUjOg GdehSheI HdGejg GdYLe QMe Gddg fGXe YbOgG eeG JYGWi GdfGS eOGe CchGHg s
(3BNQgG (B:s
(3hCeQdi HKedgG aNQLfG ef Hjf jOjg eSQhQjf hdfYeJg TGcQjf s
(3Vef eLehY s
(3ai BNQgG JYLjR dGejg GdYLe dYdi Hf eMeO Hf aQMhf GdjYeQi GdeOfis
(3GdeJhai (B746 (3g`s
(3fSNI KGdKg HChdgG Jedc eDQN Sfg (B1351s
(3gh eNJUQ TQM dGejI GdYLe ddUaOi s
(3hHBNQ UaMGJgG JYbjHg s
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs